A state-of-the-art review of intrinsic and enhanced electrical properties of asphalt materials: Theories, analyses and applications - Chen, Feng; Balieu, Romain (Materials & design, 2020)
In pavement engineering, a variety of promising application technologies are found relying on a thorough understanding of the intrinsic (mainly dielectric) electrical properties of asphalt binder and concrete materials. Meanwhile, the electrical properties of asphalt materials can be further enhanced by introducing conductive additives into and it has been brought to light that, the electrically conductive asphalt is becoming an emerging subject of interest that caters to the concept of a multifunctional pavement future. In context of these, this paper presents a holistic overview of the intrinsic and enhanced electrical properties of asphalt materials, including the theoretical analyses, as well as the corresponding applications in the practice. From such a state-of-the-art review, it is worth noting that: i) an improved understanding of asphalt material has been achieved by an in-depth examination of its electrical properties; ii) the increased significance of the research domain as a whole, and the key importance of multidisciplinary collaborations for future successes, have been indicated. [Display omitted] •The intrinsic electrical properties of asphalt binder and mixtures are not fully understood .•Bulk permittivity modelling of asphalt mixtures are critisied.•Bridge between material design and novel applications of conductive asphalt is crucial.•A multi-disciplinary future in pavement material design is emphasized.